FPGA based implementation of a perturbed Chen oscillator for secure embedded cryptosystems - Nguemo Kemdoum, Fritz; Mboupda Pone, Justin Roger; Bajaj, Mohit; Dzonde Naoussi, Serge Raoul; Ayemtsa Kuete, Gideon Pagnol; Louzazni, Mohamed; Berhanu Tuka, Milkias; Kamel, Salah (Scientific reports, 2024)
This paper introduces an enhancement to the Chen chaotic system by incorporating a constant perturbation term d to one of the state variables, aiming to improve the performance of pseudo-random number generators (PRNGs). The perturbation significantly enhances the system's chaotic properties, resulting in superior randomness and increased security. An FPGA-based realization of a perturbed Chen oscillator (PCO)-derived PRNG is presented, tailored for embedded cryptosystems and implemented on a Nexys 4 FPGA card featuring the XILINX Artix-7 XC7A100T-1CSG324C integrated chip. The Xilinx-based system generator (XSG) tool is utilized to generate a digital version of the new oscillator, minimizing resource utilization. Experimental results demonstrate that the PCO-generated data successfully passes the NIST and TestU01 test suites. Additionally, statistical tests with key sensitivity are performed, validating the suitability of the designed PRNG for cryptographic applications. This establishes the PCO as a straightforward and efficient tool for multimedia security.
Keywords: Perturbated Chen oscillator (PCO); Nexys 4 FPGA board; NIST test; Xilinx system generator (XSG); Pseudo-random number generator (PRNG); Chaotic oscillator; Field programmable gate array (FPGA)